Agricultural virtual water flows within the United States. Issue 2 (19th February 2015) - Dang, Qian; Lin, Xiaowen; Konar, Megan
Abstract: Trade plays an increasingly important role in the global food system, which is projected to be strained by population growth, economic development, and climate change. For this reason, there has been a surge of interest in the water resources embodied in international trade, referred to as "global virtual water trade." In this paper, we present a comprehensive assessment of virtual water flows within the United States (U.S.), a country with global importance as a major agricultural producer and trade power. This is the first study of domestic virtual water flows based upon intranational food transfer empirical data and it provides insight into how the properties of virtual water transfers vary across scales. We find that the volume of virtual water flows within the U.S. is equivalent to 51% of international flows, which is slightly higher than the U.S. food value and mass shares, due to the fact that water‐intensive meat commodities comprise a much larger fraction of food transfers within the U.S.. The U.S. virtual water flow network is more social, homogeneous, and equitable than the global virtual water trade network, although it is still not perfectly equitable. Importantly, a core group of U.S. States is central to the network structure, indicating that both domestic and international trade may be vulnerable to disruptive climate or economic shocks in these U.S. States. Key Points: Internal virtual water flows in the U.S. are 51% as much as global The U.S. virtual water flow network is homogeneous, social, and equitable A core group of U.S. States highlights potential network vulnerabilities